The effect of chronotype on social functioning in schizophrenic patients: examining the chain-mediating role of sleep quality and anxiety - Luo, Zheng; Zhang, Jing; Guo, Maoting; Wu, Dongmei (Frontiers in Psychiatry, 2025)
IntroductionThis study examines the relationship between chronotype and social functioning in individuals with schizophrenia, specifically assessing the mediating roles of sleep quality and anxiety symptoms.Methods785 Chinese patients with schizophrenia (aged 18-60) completed assessments using the Morningness–Eveningness Questionnaire (chronotype), Pittsburgh Sleep Quality Index (sleep quality), General Anxiety Disorder-7 (anxiety), and Personal Social Performance Scale (social functioning). Hayes’ SPSS process macros were used for analysis.ResultsSignificant associations were found, with chronotype directly impacting social functioning. Indirect mediation effects occurred through two pathways: anxiety alone, and a chain involving sleep quality and anxiety.DiscussionThese findings contribute to understanding how chronotype influences social functioning in schizophrenia, offering insights for recovery support.